(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
يهدف البحث إلى تحديد درجة ممارسة المهام الإدارية المتعلقة بوظائف الإدارة من قبل مديري رياض الأطفال الخاصة في مجالات: التخطيط, تنظيم عمل الروضة, توجيه عمل الروضة, تقويم أداء العمل. ولتحقيق أهداف البحث تمّ بناء استبانة, وتوزيعها على (65) مديراً ومديرة من مديري رياض الأطفال الخاصة في مدينة اللاذقية, وأعيد منها (59) استبانة, وبنسبة استجابة بلغت (90.77%), وبالاعتماد على الأساليب الإحصائية المناسبة تمّ التوصل إلى النتائج الآتية: 1- إنّ درجة ممارسة مديري رياض الأطفال الخاصة للمهام الإدارية في مجالات التخطيط, وتوجيه عمل الروضة, وتقويم أداء العمل هي درجة متوسطة. 2- إنّ درجة ممارسة مديري رياض الأطفال الخاصة للمهام الإدارية في مجال تنظيم عمل الروضة هي درجة عالية. 3- إنّ ممارسة الوظائف الإدارية من قبل مديري رياض الأطفال الخاصة تتم بشكل أفضل مع ازدياد سنوات الخبرة الإدارية, وارتفاع المؤهل العلمي. The research aims at determining the degree of the practice of administrative tasks related to the functions of the management by private kindergarten principals in the areas of: planning, organizing and directing the kindergarten work, and evaluating work performance. To achieve the objectives of the research, a questionnaire was done . It was distributed for (65) private kindergarten principals in the city of Lattakia, and (59) questionnaires were returned back. The response rate was (90.77%), and relying on appropriate statistical methods, results were as following: 1- This research resulted in a medium degree of the practice the principals of the private kindergarten for the administrative tasks in the field of planning, directing work to the kindergarten and evaluating of the performance. 2- The research also resulted in a high degree of the practice of the private kindergarten principals of the administrative tasks in the field of organizing the work of the kindergarten. 3- The practice of administrative functions by private kindergartens principals are better throughout the coming years of administrative experience and his being a well-qualified principal.